Assessing the effectiveness of specialized banking services (women banking, school banking, youth banking) at One Bank Limited - Mahmood, Fariha (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.